2009
DOI: 10.1177/0148607108325252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fatty Acid Composition on Th1/Th2 Polarization in Lymphocytes

Abstract: We demonstrated that differences in the composition of n-3 and n-6 polyunsaturated fatty acids, excluding eicosapentaenoic or docosahexaenoic acid, were able to influence the Th1/Th2 balance of lymphocytes in humans as well as in mice, even with normal habitual dietary intake. Background: It has become increasingly clear that polyunsaturated fatty acids (PUFAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Substitution of arachidonic acid by n‐3 LCPUFA did reduce plasma PGE 2 concentrations and may indirectly have suppressed immunoglobulin generation. Furthermore, IL‐4 and IL‐13 induce IgE isotype switching and production of these cytokines by Th2 cells as well as mast cells may be reduced by n‐3 LCPUFA . In addition, DHA was found to reduce IgE production by human B cells via the IL‐4 pathway or via an effect on CD40 .…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of arachidonic acid by n‐3 LCPUFA did reduce plasma PGE 2 concentrations and may indirectly have suppressed immunoglobulin generation. Furthermore, IL‐4 and IL‐13 induce IgE isotype switching and production of these cytokines by Th2 cells as well as mast cells may be reduced by n‐3 LCPUFA . In addition, DHA was found to reduce IgE production by human B cells via the IL‐4 pathway or via an effect on CD40 .…”
Section: Discussionmentioning
confidence: 99%
“…Wallace et al [35] have observed that feeding fish oil to mice induced a shift in the IFN-γ/IL-4 ratio by a factor of four as compared to animals fed low fat diets. Mizota et al [36] have recently conducted a very elegant study in both humans and mice that were fed n-3 PUFA enriched diets. These investigators observed that the ratio of IFN-γ/IL-4 was significantly increased after n-3 PUFA supplementation.…”
Section: T-cell Differentiation (Th1/th2 Dichotomy) and N-3 Pufamentioning
confidence: 99%
“…This becomes especially crucial during times of stress on the host [3]. Polyunsaturated fatty acids (PUFAs) have been shown to exert immune-modulating effects on the organism both in cell culture and in vivo [4]. Large concentrations of omega-6 fats are reported to have immune-suppressing effects on humans by dampening the response of the reticulo-endothelial system (RES), as well as altering neutrophil and macrophage function [3].…”
Section: Omega-6 Fatty Acidsmentioning
confidence: 99%
“…AA serves as the precursor for the eicosanoid mediators of inflammation (prostaglandins PGE2 series, leukotrienes B4 series, and thromboxanes), and when present in excess, in relation to other cell membrane lipids, it has a net impact of increase in oxidative stress on the individual [4]. Studies have found that the typical American diet consists of a ratio of up to 30:1Omega-6 to Omega-3 fats .…”
Section: Omega-6 Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation